Teacher Competencies In Implementing Deep Learning In Enjoyable Learning - Julinda Siregar; Agung Windrianto; Siti Khoirunnisa; Bunga Bunga; Yulianah Yulianah (International journal of technology and education research, 2026)
21st-century education demands that teachers possess competencies that are not only academic but also adaptive to the dynamics of deep learning. This study aims to expand on how teacher competencies influence the successful implementation of a deep learning approach in creating a fun learning environment. This study used a qualitative method with a literature review approach of more than 20 scientific articles and proceedings published between 2016 and 2025. Data collection techniques were carried out through systematic searches, and data were analyzed using thematic analysis based on narrative synthesis. The results of the study indicate that strategies such as meaningful learning, project-based learning, reflective discussions, and student collaboration can increase emotional engagement, curiosity, and long-term understanding of students. The shift in the role of teachers as facilitators is a key factor in success, although challenges such as lack of training and gaps between policy and practice remain. This study contributes to strengthening the theoretical basis of deep learning and provides practical direction for teachers and policymakers. It is recommended that further empirical research be conducted using a participatory approach to enrich understanding of the effectiveness of deep learning strategies in real-world contexts